Managing Expectations: A Case Study of Sessional Staff in Languages and Cultures Education in Australian Universities - Josh Brown; Federica Verdina (Edinburgh Napier University in collaboration with Aston University, the Universities of Dundee and Auckland, 2018)
In light of the increasing casualisation of the academic workforce in recent years, expectations of sessional staff in Australian universities from their academic employment are becoming more poignant. Following on from a previous report by Ferrari & Hajek (2012), this paper further highlights how these workers are affected by short-term, often only semester-long, contracts. We focus on how the brevity of employment affects sessional teachers' perceptions of their role and perceived obligations to the university, and consequently the health of languages education. We present the results of an online survey conducted at the vast majority of Australian universities, which investigated sessional staff's expectations. This study reveals that language sessional staff have expectations of their employment which are often at odds with their role as academics in the university environment.